2008
DOI: 10.1016/j.cellbi.2007.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stem cells isolated from the umbilical cord

Abstract: Mesenchymal stem cells (MSCs) are known as a population of multi-potential cells able to proliferate and differentiate into multiple mesodermal tissues including bone, cartilage, muscle, ligament, tendon, fat and stroma. In this study human MSCs were successfully isolated from the umbilical cords. The research characteristics of these cells, e.g., morphologic appearance, surface antigens, growth curve, cytogenetic features, cell cycle, differentiation potential and gene expression were investigated. After 2wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
153
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(159 citation statements)
references
References 26 publications
4
153
1
1
Order By: Relevance
“…This is consistent with observations made by other groups dealing with mesenchymal cells. 15,17,26 It is expected that there is no PPARg gene expression in naive CLMCs, as this gene is induced only before transcriptional activation of most adipocyte genes. 27 There is no significant difference in the intensity of gene expression among the four differentiation-treatment groups of different glucose and insulin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with observations made by other groups dealing with mesenchymal cells. 15,17,26 It is expected that there is no PPARg gene expression in naive CLMCs, as this gene is induced only before transcriptional activation of most adipocyte genes. 27 There is no significant difference in the intensity of gene expression among the four differentiation-treatment groups of different glucose and insulin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the umbilical cord (UC) is a rich source of MSCs (19). Flow cytometric analysis revealed that CD29, CD44, CD95, and CD105 were expressed on the cell surface of UC MSCs, but there was no expression of hematopoietic lineage markers, such as CD34, CD38, CD71, and HLA-DR (20). In addition, colony-forming unit fibroblast frequency was higher in UC nucleated cells than in BM nucleated cells.…”
mentioning
confidence: 99%
“…They have two very important characteristics: self-renewal and differentiation potential. Furthermore, stem cells from different organs and tissues (heart, liver, brain, bone marrow, muscles, spleen) can be derived and propagated in vitro 11,12,13,14 .…”
Section: Discussionmentioning
confidence: 99%